Studi Eksperimen Tungku Biomassa pada Proses Pengeringan Chip Umbi Porang melalui Rumah Plastik Ultra-Violet (Solar Dryer) Sistem Hibrid - Verdy A. Koehuan; Eflinda Milo; Defmit B. N. Riwu (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2022)
This study aims to determine the performance of a biomass stove with coconut shell biomass as fuel for the drying process in a hybrid system dryer house. The method used is an experimental method by testing and analyzing the efficiency of the biomass furnace and the efficiency of the drying house on the variation of the initial mass of coconut shells in the gasification chamber. The test results show that the furnace efficiency or the highest gasification efficiency occurs in combustion with an initial mass of 15 kg of coconut shell, which is 6.18%. Meanwhile, the initial mass of 12 kg and 18 kg showed furnace efficiency of 4.07% and 4.66%, respectively. The efficiency of this biomass furnace is still low, because of the pyrolysis process, which takes place at a relatively low temperature with relatively slow combustion. In the process of drying porang tuber chips through an ultra-violet plastic housing (solar dryer) this hybrid system showed a drying efficiency of 9.58% and a drying house efficiency of 30.02%. The use of biomass heat energy is 9.96%, while the largest heat energy comes from solar radiation into the drying house of 89.11%.